Lack of awareness of liver organ damage in patients with type 2 diabetes - Ciardullo, Stefano (Acta Diabetol, 2021)
AIMS: Liver steatosis, a typical finding in patients with type 2 diabetes (T2D), can lead to cirrhosis and hepatocellular carcinoma. The aim of the present study is to estimate the awareness of liver disease among patients with T2D and whether it differs according to the degree of liver fibrosis estimated by transient elastography (TE). METHODS: This is a population-based cross-sectional study. We included all patients with T2D that participated in the 2017–2018 cycle of the National Health and Nutrition Examination Survey and underwent a TE examination. Presence of liver steatosis and fibrosis was assessed by the median values of controlled attenuation parameter and liver stiffness measurement, respectively. RESULTS: Among the 825 patients included in the analysis, 8.1% (95% CI 5.1%-12.7%) of patients with steatosis were aware of having a liver condition. Even if awareness increased proportionally with increasing severity of organ damage, it remained limited even among patients with advanced fibrosis (17.9%, 95% CI 8.8%-33.3%). CONCLUSIONS: Despite increasing evidence of a frequent hepatic involvement associated with poor prognosis, awareness of suffering of advanced liver disease in patients with T2D is remarkably low, likely reflecting little recognition also among the team of health care professionals.